Biredox Eutectic Electrolytes Derived from Organic Redox‐Active Molecules: High‐Energy Storage Systems. Issue 21 (17th April 2019) - Zhang, Changkun; Qian, Yumin; Ding, Yu; Zhang, Leyuan; Guo, Xuelin; Zhao, Yu; Yu, Guihua
Abstract: One promising candidate for high‐energy storage systems is the nonaqueous redox flow battery (NARFB). However, their application is limited by low solubility of redox‐active materials and poor performance at high current density. Reported here is a new strategy, a biredox eutectic, as the sole electrolyte for NARFB to achieve a significantly higher concentration of redox‐active materials and enhance the cell performance. Without other auxiliary solvents, the biredox eutectic electrolyte is formed directly by the molecular interactions between two different redox‐active molecules. Such a unique electrolyte possesses high concentration with low viscosity (3.5 m, for N ‐butylphthalimide and 1, 1‐dimethylferrocene system) and a relatively high working voltage of 1.8 V, enabling high capacity and energy density of NARFB. The resulting high‐performance NARFB demonstrates that the biredox eutectic based strategy is potentially promising for low‐cost and high‐energy storage systems. Abstract : Busy BEE : A biredox eutectic electrolyte (BEE) is derived from the intermolecular interactions between the redox‐active molecules N ‐butylphthalimide and 1, 1‐dimethylferrocene. Given the high concentration of active materials, the flow cell based on the BEE delivers stable cycling performance, and high volumetric capacity and power density. The facile and effective strategy has potential for high‐performance nonaqueous redox flow batteries for high‐energy storage systems.